Graziacrophyma gen. nov., a new genus of South American Acanthosomatidae (Hemiptera: Heteroptera) - Carvajal, Mariom A.; Faúndez, Eduardo I.; Rider, David A. (Zootaxa, 2021)
The genus Acrophyma Bergroth currently contains two species, the Andean A. cumingii (Westwood) and the Neotropical A. bicallosa (Stål). The examination of types and new material revealed that among the Neotropical species the Brazilian population differs from the Colombian, and the first one belongs to a new species in this group. A morphological analysis of the genus indicated the Neotropical species are different from the Andean species. According to the current most used generic characters in acanthosomatids, Neotropical species should be placed in a new genus. This is also supported by biogeographical relationships. New distributional records for the species of this group are provided.